Calculation Of Fetal Weight Estimation Displayed With TFT LCD - Nadhia Regitasari; M. Ridha Mak’ruf; Endang Dian Setioningsih (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Fetal weight estimation during pregnancy is one of the beneficial ways to solve morbidity and death during labor problem. Manually, the fundal height is measured from the edge of the pubic symphysis to the top of the uterine fundus by following the arch of the uterus, using a measuring tape. The purpose of this study is to develop an easy way to count fetal weight estimation so midwives don’t have to count manually. The calculation of fetal weight estimation tool uses a variable resistor (potentiometer) as a sensor to measure the fundal height. Then it will be processed in microcontroller. The measurement results are fundal height and estimation fetal weight that will be displayed on the TFT LCD. Based on the results of measuring the fundus uterine height as much as 6 times against the measuring tool (ruler), there is no error in the device so it can be concluded that this tool can be used according to its function. This calculation of fetal weight estimation tool is portable and easy to use to help midwives count the fetal weight estimation quickly.